PENYULUHAN TENTANG PENCEGAHAN TB PARU PADA MUSIM PENGHUJAN SEBAGAI UPAYA PENGENDALIAN PENYAKIT MENULAR DI SMP NEGERI 1 ANGKOLA BARAT - Nasution, Nurul Hidayah; Harahap, Olivia Feby Mon; Harahap, Raja MP; Parlindungan, Muhammad Thohir; Nur, Muhammad; Khairunnisyah, Khairunnisyah; Nikayanti, Ria; Ritonga, Siti Meiranda Hafsari; Ardina, Lili; Siregar, Marniatun; Delima, Mas; Halawa, Sirina; Natunnah, Sofiyah; Nasution, Mutiah Dina (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2022)
Tuberculosis is an infectious disease caused by the bacterium mycobacterium tuberculosis which spreads through the air and is contracted through saliva splashes when sufferers cough, sneeze, talk and spit in any place. Tuberculosis is still a disease with a high morbidity rate. Therefore, knowledge about Pulmonary Tuberculosis and its prevention is very important as a strategy in breaking the chain of transmission of this disease, especially if it is also supported by a positive and appropriate attitude that will produce healthy behavior, so that it can assist the government in controlling disease transmission. Pulmonary Tuberculosis with maximum. This community service aims to increase youth knowledge about pulmonary TB prevention in the rainy season as an effort to control infectious diseases at Angkola Barat 1 Public Middle School. This community service activity was attended by 30 class IX students. This activity was carried out by delivering counseling materials and installing posters about pulmonary TB at SMP Negeri 1 Angkola Barat. This activity was also interspersed with discussions and questions and answers. The results of this community service activity were received enthusiastically by students. All activity participants stated that this community service was very useful because it could add insight into knowledge related to TB disease and of course affect habits in daily life.